Morphology of the oropharyngeak cavity and oesophagus of the farmed adult African catfish (Clarias gariepinus Burchell, 1822) - Ikpegbu, E. (2012)
The morphology of the adult farmed African catfish -Clarias gariepinus a prominent omnivorous cultivable species in Nigeria was investigated. It revealed cornified horny plates lining the buccal surfaces of the lips. The tongue was not free moving, and the oesophagus was a narrow tube connecting the oropharyngeal cavity to the stomach with no valve or constriction separating it from the later. Histologically, the cavity wall was lined by stratified squamous epithelium containing eosinophilic club cells, mucous cells and taste buds. The laminar propria contained dense collagen fibres. No taste bud was seen on the tongue suggesting it non involvement in food selection through gustation unlike the cavity wall which contained taste buds. The oesophagus was lined by stratified mucous epithelium containing club cells. Histochemistry revealed the presence of neutral, acid and combination of the two. The large extent of oesophageal mucification indicates need for mucin lubrication of food since teleost is known to lack salivary glands and also an adaptation to ingestion of varied feed.